Relationship Between Bitter-Taste Receptor Genotype and Solid Medication Formulation Usage Among Young Children: A Retrospective Analysis - Lipchock, Sarah V. (2012)
BACKGROUND: Children often refuse to take medication in liquid formulation because of its unpleasant taste. Recent advances in taste genetics have provided some insight into individual differences in taste among children: due to their genotype, some prefer more intense sweetness and are more sensitive to bitter tastes and thus may have different needs for medication formulation. OBJECTIVE: The aims of this study were to: (1) test the a priori hypothesis that children with the bitter-sensitive genotypes are more likely to have experienced solid medication formulations than those with the bitter-insensitive genotype; and (2) conduct post hoc analyses to examine the relationship between genotype and most preferred level of sucrose in water because sweeteners are a common component of liquid formulations. METHODS: The following data were obtained from healthy, 3- to 10-year-old children who participated in 1 of 5 taste-research studies: taste genotype for alleles of the bitter-taste receptor TAS2R38; data from retrospective reports of solid medication formulation usage and favorite beverage; and most preferred level of sucrose in water, as determined psychophysically. RESULTS: Data from 448 children were included (245 girls, 203 boys; mean age, 7.8 years). Children with ≥1 bitter-sensitive allele (TAS2R38 PP or AP genotype) were more likely to have taken medication in solid formulation than were bitter-insensitive (AA genotype) children. Children with the PP genotype preferred higher concentrations of sucrose in water, and their favorite beverage contained more grams of sugar compared with children with the AA genotype. CONCLUSIONS: Taste genotype was associated with experience with solid medication formulations and preference for more intense sweetness. This finding suggests that taste genetics might be an important factor in formulation choice and compliance in the pediatric population.